Thermohaline characteristics of coastal waters in the southern Caribbean of Costa Rica - Brenes-Rodríguez, Carlos Luis; Benavides-Morera, Rosario (Revista Ciencias Marinas y Costeras, 2015)
In August and November 2012, two hydrographic surveys were conducted in the coastal region of the Southern Caribbean of Costa Rica, between the Port of Limon and Gandoca Lagoon. A CTD (conductivity, temperature and depth profiler) was used at 43 stations to determine temperature, salinity and chlorophyll-a. It was determined that spatial and temporary variations of surface temperature were small, with values ranging between 28.6°C and 30°C. In addition, surface salinity ranged between 33.3 and 35.2 PSU and the average spatial distribution of chlorophyll-a concentration in surface waters was 0.64 mg m-3, with maximum and minimum values of 1.1 mg m-3 and 0.19 mg m-3, respectively. The vertical temperature field was characterized by a warm mixed layer (T 29°C), which extended to 60 m deep in November and less than 10 m deep in August. During the two sampled months, from the vertical structure of the isotherms, we found a cyclonic motion (from the surface to 15 m deep) in the region adjacent to Cahuita, and an anticyclonic motion at 20 m in August and 40 m in November. We identified water masses present in the water column to the depths sampled: CSW, 0-80 m and SSW, > 80 m.